الارتياح النفسي وعلاقته بالتحصيل الدراسي لدى تلاميذ السنة الرابعة ابتدائي من وجهة نظر المعلمين دراسة ميدانية لمدرستي الدني طاهر بمدينة الأغواط ومهيدي عمر بمدينة البيض - حبيب زهرة; حمداني خيرة; جلالي ناصر (My University, 2023)
This study aims to identify the issue of psychological satisfaction and its relationship to the academic achievement of fourth year primary school students from the point of view of primary stage teachers, where we try to detect the level of psychological satisfaction and its relationship to academic achievement. The study was carried out on a sample that included 149 students from the fourth year of elementary school level from my schools: Shaheed Mahidi Omar in Boualem, Wilayat El Beidh, and Taher Deni, Wilayat Laghouat. -There is a significant correlation between psychological satisfaction and academic achievement of the fourth year primary students from the teachers' point of view. -We expect a high level of psychological satisfaction among the fourth year primary students of Al-Taher Al-Dani School from the teachers' point of view. -We expect a high level of psychological satisfaction among the students of the fourth year of primary school at Mahidi Omar School from the teachers' point of view. -We expect a high level of academic achievement among the fourth year primary students of Al-Taher Al-Dani School from the teachers' point of view. -We expect an increase in the level of academic achievement among the students of the fourth year of primary school at Mahidi Omar School from the point of view of teachers. -There are differences in the psychological satisfaction of the students of the fourth year of primary school at Al-Taher Al-Dani School from the teachers' point of view. -There are differences in the psychological satisfaction of the fourth primary students of Mahidi Omar School from the teachers' point of view. -There are differences in the psychological satisfaction due to the gender variable among the students of the fourth year of primary school at Al-Taher Al-Dani School from the teachers' point of view. -There are differences in the psychological satisfaction due to the gender variable among the students of the fourth year of primary school at Mahidi Omar School from the point of view of the teachers. -There are differences in the academic achievement due to the gender variable among the fourth year primary students of Al-Taher Al-Dani School from the teachers' point of view.